Prospects of Drug Interaction of Metformin with Lifesaving Hypertensive Drugs in Type2 Diabetic Patients. A Clinical Comparative Study - Naveed Shuja, Naheed Akhter, Shahnaz Bano Memon, Fareeda Islam, Qamar Zaman Phull, Mashkoor Ahmed Ansari (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of current study was to check and concluded the chances of any drug interaction of metformin with hypertensive treatment with beta- blockers and calcium channel blockers in type 2 diabetic patients. During study diabetic patients with type 2 were treated with metformin and hypertensive drugs i.e. beta- blockers and calcium channel blockers. There is no any drug interaction in both gender has seen (1.00± 00.01, 1.00± 00.01). while Significant change (p<0.05) regarding glucose levels, systolic and diastolic blood pressure were seen in group B and group C as compared to the group A i.e. control group.